1995
DOI: 10.1021/j100022a024
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Energy Surface for Activation of Methane by Co+: An Experimental Study

Abstract: A guided-ion-beam mass spectrometer is used to study the reactions of Co+ + CD4 and CoCH2+ + D2 and thereby experimentally probe the potential energy surface for activation of methane by Co+. The results obtained are compared to recent theoretical results and agree with the conclusion that dehydrogenation of methane by Co+ is hindered by a tight four-center transition state complex. The major discrepancy observed between experiment and theory is in the height of this barrier, which theory predicts is 96-109 kJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
117
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(133 citation statements)
references
References 11 publications
(16 reference statements)
14
117
2
Order By: Relevance
“…From Eq. (14), D 0 (D-CD 3 ) = 4.58 eV, and a calculated zero-point energy difference between IrD + and IrH + of 0.041 ± 0.004 eV, this predicts a threshold of 1.42 ± 0.06 eV for formation of IrD + in reaction (2). Our analysis of this cross section (Table 1) measures a somewhat higher threshold of 1.69 ± 0.07 eV.…”
Section: Ir + -Hmentioning
confidence: 64%
See 2 more Smart Citations
“…From Eq. (14), D 0 (D-CD 3 ) = 4.58 eV, and a calculated zero-point energy difference between IrD + and IrH + of 0.041 ± 0.004 eV, this predicts a threshold of 1.42 ± 0.06 eV for formation of IrD + in reaction (2). Our analysis of this cross section (Table 1) measures a somewhat higher threshold of 1.69 ± 0.07 eV.…”
Section: Ir + -Hmentioning
confidence: 64%
“…Formation of IrD 2 + has the highest threshold of all processes observed, which is consistent with formation of the high-energy CD 2 neutral. The formation of MD 2 + product ions is unusual and has not been detected for reaction of methane with first-row [8][9][10][12][13][14][15]18], second-row [7,11,[16][17][18], and several thirdrow (La + , W + , Re + , Lu + ) transition metal ions [18,20,21]. However, this product has been observed in reactions of methane with Pt + [19].…”
Section: Reactions Of Ir + With Methanementioning
confidence: 94%
See 1 more Smart Citation
“…There is a growing body of experimental information regarding the interactions of small neutral 1 and cationic [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] clusters of transition metals with compounds containing prototypical bonds ͑e.g., C-H, C-C, N-H, O-H, Si-H, Si-C͒ of importance in catalytic processes. Transition metal-main group complexes have been the focus of intense computational effort.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we believe that errors resulting from relativistic effects are much less than those due to incomplete basis sets and can be safely neglected. [51] and Co , [52] including detailed reaction mechanisms and PESs, were reported by Armentrout et al [11,12] They identified the four-centered TS shown in Scheme 1 (top). More recently, they also studied the reaction mechanism of Sc with CH 4 by using the CASSCF and MR-SDCI-CASSCF methods.…”
Section: Ionization Potential Of Scandiummentioning
confidence: 99%